SuperHyperSoft Set-Based Evaluation of Teaching Quality in Ideological and Political Courses in Colleges and Universities in the New Era - Ningning Wang; Zheng Zhao (Neutrosophic Sets and Systems)
In the new era, the quality of ideological and political education in colleges and universities has become a vital focus for nurturing responsible, critically thinking citizens. The rapid evolution of societal needs, coupled with technological advancements, demands a fresh evaluation of teaching effectiveness in these fundamental courses. Traditional evaluation models often struggle to address the uncertainty, complexity, and overlapping nature of qualitative educational indicators. This paper introduces a novel evaluation framework based on SuperHyperSoft Set theory integrated with Single-Valued Neutrosophic Sets (SVNS), combined with Entropy for objective weighting and the MOOSRA method for robust ranking of alternatives. The proposed framework provides a structured, flexible, and uncertainty-resilient approach to evaluating teaching quality. A real-world case study is conducted involving five major political science and ideological courses at a leading university. Expert evaluations were collected, processed using the SuperHyperSoft-SVNS model, and analyzed to identify strengths and areas for improvement. The results demonstrate the model’s ability to capture complex educational dynamics and offer practical insights for enhancing teaching practices in the new era.